COMPARISON OF SPERM ATTRIBUTES IN FROZEN THAWED SEMEN OF PURE AND CROSSBRED JERSEY BULLS - KUMAR, U; GAWANDE, A P; SAHATPURE, S K; PATI, P; RAJAK, S K (The Indian Journal of Animal Reproduction, 2016)
Thirty-six ejaculates (3 ejaculates / bull) of pure and crossbred Jersey bulls were used to compare sperm attributes of frozen thawed semen. The seminal attributes viz. semen volume, sperm concentration, post thaw motility and acrosome integrity were similar (p>0.05) between the breeds, whereas, the percentage of live sperm during post thaw period were higher (p0.05) between pure and crossbred Jersey bulls, however, the proportion of detached / free head, bent mid piece, free tail and highly coiled tail was higher (p0.05) and acrosomal integrity (p
Keywords: Crossbred; Jersey bull; Semen; Sperm abnormality; Sperm attributes